(untitled) (Altre Modernità, 2016)
The article analyses the utilization of Cesare Lombroso as a character in some recent novels, in the wake of the renewed interest in his personality and his work that has occurred over the past decade. The analysis is focussed in particular on the specific features of Lombroso the scientist that are more commonly foregrounded by novelists. The aim is to establish whether such narrative fiction can contribute to a novel interpretation of the core aspects of Lombroso’s work - namely the complex relationship between crime, social control and construction of a national identity - or whether the scientific aspects lose significance.